'Nervous' Immunity: Walking the Tightrope. Issue 5 (May 2020) - Kulkarni, Subhash; Kurapati, Sravya; Bogunovic, Milena
Abstract : There is a major gap in our understanding of how the intestinal immune and nervous systems are integrated to regulate protective adaptations to enteric infections while maintaining tissue homeostasis. Three recent complementary reports published in Cell (2020) provide new mechanistic insights into how this enteric neuro-immune crosstalk may occur.